Breeding a pasture and feed legume adapted to subacid Italian Mediterranean areas: the blue lupin - Bozzini A.; Chiaretti D. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
Lupinus angustifolius L. (blue lupin) is a Mediterranean wild species growing profusely in subacid, sandy or volcanic soils, particularly of Tyrrhenian Italy. These wild types are well adapted to poor, marginal soils, mainly used for cereals and for pastures for ruminants. A breeding programme has been developed to select domesticated lines mainly by tranferring domestication characters present in cvs bred in Australia and Poland into 3 Italian wild selections, highly adapted to Central and South Italy and highly productive. Several crosses were made and selection performed for desired genetic traits. Results of the research and main characteristics of the new selections for high biomass and seed production are reported.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)